A study of the response of depleted type p-MOSFETs to electron dose - Fragopoulou, M.; Stoulos, S.; Zamani, M.; Benton, E.; O'Sullivan, D.; Siskos, S.; Laopoulos, T.; Konstantakos, v.; Sarrabayrouse, G. (HNPS Advances in Nuclear Physics, 2019)
The p-MOSFET dosimeter studied in this work has been manufactured at LAAS- CNRS Laboratory in Toulouse France, for applications in personal and space dosimetry. They are proposed for proton, heavy ions and electron and photon dose measurements. The current study investigates the sensitivity of this new type of Metal-Oxide-Semiconductor field effect transistor (MOSFET) to electrons. The sensitivity of the new MOSFET based dosemeters to electrons is linear for wide dose ranges. The influence of the electrons energy on the dosemeters response is also investigated.